Respuesta :
4x + 6y = 36...reduce........2x + 3y = 18
5y - 3x = 49...rearrange...-3x + 5y = 49
2x + 3y = 18 ...multiply by 3
-3x + 5y = 49 ..multiply by 2
--------------
6x + 9y = 54 (result of multiplying by 3)
-6x + 10y = 98 (result of multiplying by 2)
--------------add
19y = 152
y = 152/19
y = 8
2x + 3y = 18
2x + 3(8) = 18
2x + 24 = 18
2x = 18 - 24
2x = - 6
x = -6/2
x = -3
first number is -3, second number is 8
5y - 3x = 49...rearrange...-3x + 5y = 49
2x + 3y = 18 ...multiply by 3
-3x + 5y = 49 ..multiply by 2
--------------
6x + 9y = 54 (result of multiplying by 3)
-6x + 10y = 98 (result of multiplying by 2)
--------------add
19y = 152
y = 152/19
y = 8
2x + 3y = 18
2x + 3(8) = 18
2x + 24 = 18
2x = 18 - 24
2x = - 6
x = -6/2
x = -3
first number is -3, second number is 8
Answer:
-3 and 8
Step-by-step explanation:
4x + 6y = 36
2x + 3y = 185
y - 3x = 49
-3x + 5y = 49
2x + 3y = 18
3-3x + 5y = 49
6x + 9y = 54
-6x + 10y = 98
19y = 152y = 152/19y = 82x + 3y = 182x + 3(8) = 182x + 24 = 182x = 18 - 242x = - 6x = -6/2x = -3